Roles of p53 and p27 (Kip1) in the regulation of neurogenesis in the murine adult subventricular zone - Gil-Perotin, Sara (2011)
The tumor suppressor protein p53 (Trp53) and the cell cycle inhibitor p27 (Kip1) (Cdknb1) have both been implicated in regulating proliferation of adult subventricular zone (aSVZ) cells. We previously reported that genetic ablation of Trp53 (Trp53 (−/−)) or Cdknb1 (p27 (Kip1−/−)) increased proliferation of cells in the aSVZ, but differentially affected the number of adult born neuroblasts. We therefore hypothesized that these molecules might play non-redundant roles. To test this hypothesis we generated mice lacking both genes (Trp53 (−/−);p27 (Kip1−/−)) and analysed the consequences on aSVZ cells and adult neuroblasts. Proliferation and self-renewal of cultured aSVZ cells were increased in the double mutants compared with control, but the mice did not develop spontaneous brain tumors. In contrast, the number of adult-born neuroblasts in the double mutants was similar to wild-type animals and suggested a complementation of the p27 (Kip1−/−) phenotype due to loss of Trp53. Cellular differences detected in the aSVZ correlated with cellular changes in the olfactory bulb and behavioral data on novel odor recognition. The exploration time for new odors was reduced in p27 (Kip1−/−) mice, increased in Trp53 (−/−) mice and normalized in the double Trp53(−/−);p27 (Kip1−/−) mutants. At the molecular level, Trp53 (−/−) aSVZ cells were characterized by higher levels of NeuroD and Math3 and by the ability to generate neurons more readily. In contrast, p27 (Kip1−/−) cells generated fewer neurons, due to enhanced proteasomal degradation of pro-neural transcription factors. Together, these results suggest that p27 (Kip1) and p53 function non-redundantly to modulate proliferation and self-renewal of aSVZ cells and antagonistically in regulating adult neurogenesis.